Sequestration of doxycycline and mefenamic acid from liquid phase using 1,3-diaminopropane modified poly(acrylonitrile-acrylic acid): isotherm, kinetic and mechanism studies - Fatimah Lee,; Siti Nurul Ain Md Jamil,; Nur Nida Syamimi Subri,; Abel Adekanmi Adeyi,; Rusli Daik, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Accumulation of pharmaceutical residues in aquatic environment due to daily consumption by humans and animals for diseases treatment results in alarming long-term effects. This study evaluates the adsorption potential of a polymer-based adsorbent, 1,3-diaminopropane-modified poly(acrylonitrile-acrylic acid) (DAP-poly(ACN/AA)), for the uptake of doxycycline (DOX) and mefenamic acid (MEFA) from aqueous solution. The chemical modification of poly(ACN/AA) copolymer with DAP was successful as suggested by the FTIR spectra and microanalysis results. The SEM analysis showed that the modified copolymer has larger particle size, which was 156 nm as compared to that of poly(ACN/AA) copolymer (133 nm). The influence of adsorbent dosage, contact time, pH and initial concentration on the adsorption of DOX and MEFA compounds were investigated. The kinetic studies of DOX and MEFA was fitted well to pseudo-second-order model with chemisorption being the rate-controlling step. The equilibrium isotherm has its fitness in the following order: Langmuir model > Freundlich model > Temkin model. The maximum adsorption capacities for DOX and MEFA were 210.4 mg/g and 313.7 mg/g, respectively. The excellent high sorption capacity suggest that DAP-modified poly(ACN/AA) copolymer is a potential adsorbent for the treatment of DOX and MEFA bearing effluent in adsorption system.